RNA‐Seq analysis of potential lncRNAs and genes for the anti‐renal fibrotic effect of norcantharidin. Issue 10 (19th May 2019) - Xiao, Hengting; Liao, Yingjun; Tang, Chengyuan; Xiao, Zheng; Luo, Hanwen; Li, Jun; Liu, Hong; Sun, Lin; Zeng, Dong; Li, Ying
Abstract: Background: As a common phenotype in chronic kidney disease, renal interstitial fibrosis has been largely studied. Norcantharidin (NCTD), a derivative of naturally occurring cantharidin, has an anti‐renal fibrotic effect. However, its underlying mechanisms of the protective role remain largely unknown. Long noncoding RNAs (lncRNAs) play vital parts in tissue homeostasis modulation under pathophysiological conditions. In this study, we discovered the underlying lncRNAs and genes, which may contribute to the anti‐renal fibrotic effects of NCTD. Methods: RNA‐seq analysis was performed to evaluate profiling of lncRNAs and messenger RNAs (mRNAs) in kidney tissues of sham‐control, and unilateral ureteral obstruction (UUO) mouse models with or without NCTD treatment. Systematic bioinformatic analysis of expression levels was used in lncRNAs and mRNAs of NCTD‐treated UUO kidneys. Altered expression of lncRNAs and mRNAs levels was confirmed by quantitative real‐time polymerase chain reaction analysis. Results: 467 lncRNAs and 1502 mRNAs were differentially expressed between UUO‐ and sham‐operated kidneys, and notably, these alterations in UUO‐operated kidney were partially reversed following NCTD treatment. Interestingly, the up‐regulation of lncRNA Gm16076, Gm26669, and down‐regulation of Fam120aos were highly correlated with the up‐regulation of mRNA levels of fibrosis‐related gene ITGB1, STAT3 and reduction of Pink1 in UUO kidney, respectively. Conclusions: The result suggested lncRNAs‐regulated genes may contribute to the anti‐renal fibrotic effect under NCTD treatment, and thus targeting lncRNAs‐controlled genes and their related molecular signaling pathways may serve as a promising therapeutic target in renal fibrosis treatment. Abstract : In conclusion, we identified a set of norcantharidin (NCTD)‐regulated long noncoding RNAs (lncRNAs) and messenger RNAs (mRNAs), whose altered expression may contribute to the anti‐fibrotic effect of NCTD. Among these NCTD‐regulated genes, we found that the lncRNA Gm16076, Fam120aos, Gm26669, and their potential targets (ITGB1, STAT3, and Pink1) appear to be critical in the pathogenesis of renal interstitial fibrosis. Thus targeting lncRNAs‐controlled genes and their regulated signaling pathways may serve as a therapeutic approach for renal fibrosis.